High Patient Catastrophizing Score Predicts Poor Outcome in the Complex Foot and Ankle Patient. Issue 4 (16th October 2019) - Gagné, Oliver; Veljkovic, Andrea; Anderson, Lindsay; Symes, Michael; Abbas, Kaniza Zahra; Penner, Murray J; Wing, Kevin; Younger, Alastair S.E.; Syed, Khalid; Lau, Johnny T.C.
Category: Ankle Introduction/Purpose: Patients perspective and experience is heavily modulated by their understanding of their pre-operative disability along with their overall coping strategy and life philosophy. It is well appreciated that patient's catastrophization and emphasis on outcomes can affect their outcome. Given that we are relying on patient-reported outcomes more and more, the orthopedic community must be diligent in differencing patients that may have the same objective outcome vary widely on a patient-centered subjective basis. Catastrophization has been reported to affect outcomes in the arthroplasty litterature and this was the first study to look at its effect in the foot and ankle world. Methods: This current study set out to look at a cohort of complex consecutive foot and ankle cases and describe the relationship between Patient Catastrophizing Score (PCS) and multiple functional outcomes that are used routinely. The PCS has three subcategory rumination, helplessness and magnification. In the end, 46 patients were found to be eligible in the study with an average age of 54.72 ± 14.41 years-old, a majority female 30 / 46 (65.22%), a minority employed at the pre-operative visit 19/46 (41%) and with an average BMI of 26.2 ± 5.56. We used univariate and multivariate regression analysis for further statistical analysis. Results: We found that the mental component of the SF12 had a statistically significant negative effect with the rumination score (-1.03) and the helplessness score (-1.05). There was no statistically significant effect for the physical component of the SF-12. Looking at the FAOS Pain component, it correlated with the PCS rumination and helplessness. Otherwise the FAOS ADL component showed correlation as well with the PCS rumination (M -4.67 (p=0.02) U: -1.85 (0.01)), helplessness (M -5.89 (p = 0.01) U -1.81 (p = 0.001)) and total score (M: 3.74 (p=0.02) U -0.75 (p=0.01)). The FAOS Quality of life component was statistically significant for the rumination score (-11.59) (p > 0.05) and the helplessness score (-9.65) (p = 0.002) also the PCS total (8.54). Conclusion: This study confirms that post-operative patient reported outcome (SF- 12MCS, FAOS) are affected by pre-operative catastrophization scores. This has extensive implications in the patient selection, counselling and tailoring of surgeries offered to patients. This is also a symbolic finding highlighting that certain outcomes measure need to be adjusted or updated. This was a pilot study to capture the initial trend and within the limits of our methodology we would recommend future larger study trials and careful pre-operative selection based on PCS scores.